Strategy on the production of bead free electrospun gelatin scaffolds - Chung, She Man; Weily, Khoo; Lim, Shing Chee; Zakaria, Mohd Faiz; Koh, Ching Theng (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM, 2018)
Electrospun scaffolds consist of micro-scale or nano-scale porous fibrous networks. These electrospun scaffolds had become increasingly popular in tissue engineering filed as it could provide nano-environment for cell culture and produced by using biodegrable polymer. One of the important key to provide such environment for cell culture is the porosity of the electrospun scaffolds as it is highly related with the cell-cell interaction. The porosity of the electrospun scaffolds could be affected by bead formation which is one of the common problems faced in electrospinning process. However, the formation of beads are difficult to be controlled as it depends on environmental factors such as humidity and operating temperature. Controlling these two environmental factors normally requires an expensive control system. This paper aims to solve the problem of bead formation by adjusting material concentration and process parameters without controlling the environmental factors. The parameters studied in this paper include polymer concentration, flow rate, distance between the syringe needle tip and collector and applied voltage. The microstructure of the electrospun scaffolds produced were visualised using scanning electron microscopy (SEM) and were analysed in terms of bead formation and fiber diameter. This study shows that polymer concentration is the best strategy to prevent bead formation in gelatin scaffolds while other process parameters such as applied voltage, distance between the syringe needle tip and the collector as well as flow rate can be used to control the fiber diameter. An understanding of the effects of each parameter provides a guideline to control microstructure morphology by producing bead-free electrospun gelatin scaffolds.